2022
DOI: 10.1097/01.ogx.0000827232.41429.82
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Smartphone App to Explore Potential Underuse of Prophylactic Aspirin for Preeclampsia

Abstract: Preeclampsia is a leading factor associated with maternal and neonatal morbidity and mortality. Effective prophylaxis can be achieved with low-dose aspirin (LDASA) 75 to 150 mg daily during pregnancy if initiated early in moderate-to high-risk patients. The US Preventive Services Task Force (USPSTF) has a documented set of criteria for LDASA consideration in the presence of 1 or more high or 2 or more moderate-risk factors. The practical usage of these guidelines are associated with challenges including incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Physicians (residents/fellows and attendings) in this study reported that shared decision-making with the patient was a barrier to providing preventive EOP care, which is consistent with a study conducted among pregnant Medicaid beneficiaries. 10 This sentiment was more common among residents/fellows than attending physicians, which could be attributed to the lack of continuity of care in the resident clinics at our institution. A study published in 2021 found that the use of a smartphone app with data shared between patient and provider improved both the patient's and provider's ability to identify and manage risk factors for EOP.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Physicians (residents/fellows and attendings) in this study reported that shared decision-making with the patient was a barrier to providing preventive EOP care, which is consistent with a study conducted among pregnant Medicaid beneficiaries. 10 This sentiment was more common among residents/fellows than attending physicians, which could be attributed to the lack of continuity of care in the resident clinics at our institution. A study published in 2021 found that the use of a smartphone app with data shared between patient and provider improved both the patient's and provider's ability to identify and manage risk factors for EOP.…”
Section: Discussionmentioning
confidence: 90%
“…A study published in 2021 found that the use of a smartphone app with data shared between patient and provider improved both the patient's and provider's ability to identify and manage risk factors for EOP. 10 An intervention similar to this could be a strategy to increase shared decision-making between patient and provider, which could be especially impactful in clinics with low continuity of care.…”
Section: Discussionmentioning
confidence: 99%
“…Duarte-Rojo et al developed a smartphone app for cirrhosis patients, with educational and exercise videos of an appropriate intensity, to provide assisted rehabilitation and remote supervision [43]. Krishnamurti et al designed an antenatal care smartphone app to enhance the identification of patients at risk for preeclampsia [44]. Mobile applications have also been increasingly important in dermatology in recent years [45].…”
Section: Related Workmentioning
confidence: 99%